2015
DOI: 10.1186/1748-7161-10-s2-s2
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis corrective force estimation from the implanted rod deformation using 3D-FEM analysis

Abstract: BackgroundImprovement of material property in spinal instrumentation has brought better deformity correction in scoliosis surgery in recent years. The increase of mechanical strength in instruments directly means the increase of force, which acts on bone-implant interface during scoliosis surgery. However, the actual correction force during the correction maneuver and safety margin of pull out force on each screw were not well known. In the present study, estimated corrective forces and pull out forces were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Therefore, the strengths and clinical relevance of this study are that it showed that a lower axial trajectory and a high screw pull-out force during rod connection might be crucial risk factors for PPS loosening in clinical situations. A rod reduction device has been reported as the cause for screws to be pulled toward the rigid rod, causing a failure of the screw-bone interface in deformity-correction surgery 23,24) . Our study indicated that this pull-out force toward the rod in the PPS system might be a risk factor for screw pull-out during rod connection, especially at the LIV.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the strengths and clinical relevance of this study are that it showed that a lower axial trajectory and a high screw pull-out force during rod connection might be crucial risk factors for PPS loosening in clinical situations. A rod reduction device has been reported as the cause for screws to be pulled toward the rigid rod, causing a failure of the screw-bone interface in deformity-correction surgery 23,24) . Our study indicated that this pull-out force toward the rod in the PPS system might be a risk factor for screw pull-out during rod connection, especially at the LIV.…”
Section: Discussionmentioning
confidence: 99%
“…Destabilization of the posterior spinal segment by releasing soft tissue or facet joints could be important to prevent implant breakage or pedicle fracture during maneuver in more severe curve corrections [18]. However, it is still unclear whether these posterior releases positively affect the TK, especially with a hyphokyphotic thoracic spine [1,9].…”
Section: Discussionmentioning
confidence: 99%
“…Although destabilization of the posterior spinal segment by releasing the soft tissue or facet joints could be important to prevent implant breakage or spinal fracture during maneuvers in curve corrections, it is important for maintenance of fatigue strength to avoid intraoperative notches on the rods, because rod failure would be facilitated by pseudarthrosis . When stress concentrations are introduced in the form of notches, these play a major role in fatigue strength, since rod fractures almost always occur at these initiation points of increased stress .…”
Section: Discussionmentioning
confidence: 99%